Dosis de pollinaza en el rendimiento del forraje de Vigna unguiculata L. chiclayo verdura y Pennisetum sp. cuba 22, en asociación. Loreto - Ruiz Da Silva, Luisa Valeria (2024)
The association of Poaceae with Fabaceae is one of the ways to improve the yield and quality of forage for feeding polygastric animals. The Faculty of Agronomy of the National University of the Peruvian Amazon is concerned with carrying out research work in the humid tropics and this document is titled DOSE OF POLLINCOAT IN THE YIELD OF FORAGE OF Vigna unguiculata L. CHICLAYO VEGETABLES AND Pennisetum sp. CUBA 22, IN ASSOCIATION. LORETO. A completely randomized block design was used with an experimental unit area of 3.6 m2, the treatments were T0 (control), T1 (10 tons of chicken manure/ha), T2 (20 tons of chicken manure/ha and T3 (30 tons of manure/ha) the following conclusions were reached that the association of Vigna unguiculata L. “Chiclayo verdura” with Pennisetum sp. “Cuba 22” reacted positively to the highest dose of manure applied. It is recommended to use the T3 treatment (30 tons. of manure/ha) since it was better in the dependent variables in the study such as height of 1.75 meters, green matter of 5.05 kg/m2, weight of leaves of 2.47 kg/m2, weight of stems of 2.58 kg/m2 and dry matter of. 1.01 kg/m2. The yield of green matter was 50.5 tons per hectare of associated biomass.